Kebijakan Penangguangan Tindak Pidana Cyberstalking pada Media Elektronik - Rumlus, Muhamad Hasan; Kusmiadi, Moh Ery; Rajab, Adirandi M; Pamungkas, Agfajrina Cindra (Program Studi Hukum Universitas Pendidikan Muhammadiyah Sorong, 2023)
Abstract In this article, will answer the importance of establishing a firm and comprehensive law in tackling cyberstalking crimes in Indonesia. This problem arises from the lack of clarity in the current regulation regarding the protection of everyone from stalking. So far, Indonesia does not have a law specifically dealing with cyberstalking crimes. The research used by the author in this study is a normative juridical research method, which is a research method with a focus on the study of the application of norms in positive law. in Indonesia the handling of stalking acts carried out by stalkers is still unclear, or explicit, the rules used to tackle stalking acts still use Article 351 paragraph 1 of the Criminal Code, Article 29 jo. Article 45 Paragraph (3) of the ITE Law, Article 27 paragraph (3), and Article 115 j.o. 12 Copyright Law. Nevertheless, the Article is still felt to be ineffective. So it is deemed necessary to immediately ratify a law related to protection from stalker actions so that it can provide security and a sense of security in carrying out life in a society. Keywords: Crime, Cyberstalking, Policy